Motivasi Perempuan Berwirausaha Produk Pertanian di Pasar Adat Tegal Darmasaba, Kecamatan Abiansemal, Kabupaten Badung - PUTRI, MADE ADELINA WIMA; RANTAU, I KETUT; SARJANA, I DEWA GEDE RAKA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.10, No.2, Desember 2021, 2021)
Motivation of Women to Sell Agricultural Products in Tegal Darmasaba Traditional Market, Abiansemal District, Badung Regency It is difficult to find a job because of the increasingly fierce competition in job seeking, which requires particular skills. Many decide to become entrepreneurs and create their own opportunity to work rather than relying on others to provide jobs. Given the limited employment opportunities currently available, it is important to encourage everyone, including women to become entrepreneurs. This study aims to analyze the level of motivation of women who are entrepreneurs of agricultural products in the Tegal Darmasaba Traditional Market, Abiansemal District, Badung Regency. The data used are primary data as the main data obtained by distributing questionnaires to 36 women traders in the Tegal Darmasaba Traditional Market. Secondary data are obtained from literature in the form of books, previous research, and other sources. The data analysis technique used in this research is descriptive analysis. The results show that the level of motivation for women in entrepreneurship in agricultural products in the Tegal Darmasaba Traditional Market is quite low with a percentage of 47,22 percent. Most of the women are vegetable traders with a percentage of 52.78 percent. Therefore, the government should implement policies and programs that support SME business activities to improve the welfare of women entrepreneurs.